Effect Of Job Description And Work Commitment On The Work Achievement Of Employees Of Pt. Mandiri Berjaya Abadi Medan - Wilbert Wilbert; Thomas Sumarsan Goh; Wily Julitawaty; Syawaluddin (Institute of Computer Science (IOCS), 2022)
A job description is a written statement about the description of a job, its conditions, and relationships with other parts of the organization. Job descriptions are an important part of the human resource development system. Work commitment is an attitude that shows more than just formal membership, but also includes an attitude of liking the organization and a willingness to put forth a high level of effort for the benefit of the organization in order to achieve its goals. Work performance or work performance is defined as an expression of ability based on knowledge, attitudes and skills, and motivation in producing something. This research uses quantitative descriptive research. The sampling technique used a saturated sample. The research scale used is a Likert scale. Simultaneously there is a significant influence between the variable job description and work commitment to the work performance of employees of PT. Mandiri Berjaya Abadi. While partially found the variable job description has a significant effect on the work performance of employees of PT. Mandiri Berjaya Abadi. Partially, it was found that the work commitment variable had a significant effect on the work performance of PT. Mandiri Berjaya Abadi